A Consistent Data Series to Evaluate Growth and Inequality in the National Accounts. (9th November 2017) - Fixler, Dennis; Johnson, David; Craig, Andrew; Furlong, Kevin
Abstract : Recent headlines frequently refer to rising inequality and its implication on economic growth and social welfare. Addressing the latter is difficult and requires more than simply looking at GDP, as Kuznets long ago pointed out. In this paper we focus on the importance of the income measure underlying the inequality measure when examining the relationship between GDP growth and inequality. We create a mapping using Census Bureau household survey data and Bureau of Labor Statistics (BLS) consumer expenditure data to create distributional measures of the Bureau of Economic Analysis (BEA) personal income. We show that for the period 2000‐2012, inequality using personal income is substantively lower than inequality measured using Census Bureau money income, and the trends in both inequality and median income are different. This demonstrates the importance of using a measure a national accounts based measure of income when examining the relationships between inequality and growth.